Genetics of Leukocyte Telomere Length and its Role in Atherosclerosis - Aviv, Abraham (2011)
Humans display a large inter-individual variation in leukocyte telomere length (LTL), which is influenced by heredity, sex, race/ethnicity, paternal age at conception and environmental exposures. LTL dynamics (birth LTL and its age-dependent attrition thereafter) mirror telomere dynamics in hematopoietic stem cells (HSCs). LTL at birth is evidently a major determinant of LTL throughout the human lifespan, such that individuals endowed with short (or long) LTL at birth probably have short (or long) LTL later in life. Therefore, the associations of short LTL with atherosclerosis and with diminished survival in the elderly may relate to short birth LTL, accelerated age-dependent LTL attrition, or both. The mechanisms underlying these associations are still not well understood, but they stem in part from genetic factors in control of telomere maintenance and the rate of HSC replication.